Communicating radon risk via a smartphone app: a pilot intervention study - Soojung Kim; Michael S. Brewster; Gary G. Schwartz (BMC, 2020)
Abstract Background Residential radon is a major preventable cause of lung cancer. However, prevention requires radon testing and it has proven very challenging to motivate individuals to test their homes for hazards like radon that are invisible and whose health effects occur after a long latency following exposure. Novel approaches to radon communication are urgently needed. Methods We created a novel radon-education app for smartphones and examined its effectiveness in increasing radon knowledge and radon testing. We studied radon knowledge and attitudes and behavior relevant to radon testing before and after app use. Results Ninety-seven undergraduates installed the app on their smartphones and used it for a month. App use resulted in higher scores in the domains of radon knowledge (p < .001); self-efficacy (p < .001), and response efficacy (p < .001). Twenty-three participants (24%) used the app to obtain a free radon test kit. Self-efficacy (p < .05) and response efficacy (p < .01) were positive predictors of ordering a test kit. The test process completion rate (the fraction of participants who ordered test kits, used them to test their houses and sent the kits to the lab) was 9%. Conclusions A smartphone app is a promising venue for communicating radon risk and for stimulating radon testing. Future interventions designed to increase actual test kit use are required to maximize the benefit of the app.